Host community composition, community assembly pattern, and disease transmission mode jointly determine the direction and strength of the diversity-disease relationship - Chen, Lifan; Kong, Ping; Hou, Liying; Zhou, Yanli; Zhou, Liang (Frontiers in Ecology and Evolution, 2022)
Rapid global biodiversity loss and increasing emerging infectious diseases underscore the significance of identifying the diversity-disease relationship. Although experimental evidence supports the existence of dilution effects in several natural ecosystems, we still know very little about the conditions under which a dilution effect will occur. Using a multi-host SIR model, we found that the diversity-disease relationship could exhibit an increasing, decreasing, or non-monotonic trend when disease transmission was density-dependent, which mainly depended on the patterns of community assembly. However, the combined effect of the host competence-abundance relationship and species extinction mode may reverse or weaken this trend. In contrast, when disease transmission was frequency-dependent, the diversity-disease relationship only showed a decreasing trend. Although the host competence-abundance relationship did not alter this decreasing trend, it could reduce the detectability of this trend and affect disease prevalence. Overall, a combination of disease transmission mode, community assembly pattern, and host community composition determines the direction or strength of the diversity-disease relationship. Our work helps to explain why some experiment studies came to different conclusions about the dilution effect and contributes to a deeper understanding of the dynamics of pathogen transmission in communities.